1998
DOI: 10.1074/jbc.273.34.21505
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-specific Interactions of Cyanide with the N-Methyl-d-aspartate Receptor

Abstract: Cyanide is a mitochondrial poison that adversely affects cellular respiration by inhibiting the reoxidation of cytochrome a 3 by molecular oxygen, thereby obstructing the electron transport chain and oxidative phosphorylation (1). Cytochrome a 3 and cytochrome a form the cytochrome c oxidase complex, which is the terminal enzyme in the electron transport chain. Transferring electrons to oxygen, cytochrome c oxidase is the cellular respiratory component responsible for the critical need for oxygen. Thus, cyanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…7), because cyanide also modulates NMDA receptor activation (Patel et al, 1994;Arden et al, 1998). Solution containing iodoacetate and cyanide (1 mM) and lacking O 2 and glucose produced an AD (Fig.…”
Section: Blocking Mitochondria With Cyanide Gives An Earlier Ad Than mentioning
confidence: 96%
See 2 more Smart Citations
“…7), because cyanide also modulates NMDA receptor activation (Patel et al, 1994;Arden et al, 1998). Solution containing iodoacetate and cyanide (1 mM) and lacking O 2 and glucose produced an AD (Fig.…”
Section: Blocking Mitochondria With Cyanide Gives An Earlier Ad Than mentioning
confidence: 96%
“…The potentiating action of cyanide on NMDA receptors containing NR2A subunits (Patel et al, 1994;Arden et al, 1998), together with the fact that the AD is mostly produced by activation of NMDA receptors (Rossi et al, 2000), seems a likely explanation for this slight acceleration.…”
Section: Comparison Of Cyanide and Rotenone/antimycin As Mitochondriamentioning
confidence: 97%
See 1 more Smart Citation
“…Because NEM pretreatment blocks the cyanide action on NMDA receptor responses, it is concluded that activation of the redox sites is necessary for the manifestation of cyanide's effect. Recently, Arden et al (18) showed that cyanide potentiates NMDA receptor-mediated whole cell currents in rat cortical neurons. As in the present study, this action was explained by cyanide interacting with putative redox-active sites on the receptor subunits by cyanolating cysteine residues to form thiocyanate adducts.…”
Section: Discussionmentioning
confidence: 99%
“…Because the enhancement persists in cell-free patches, it is likely that the response results at least in part from direct interaction with the receptor. Recently, Arden et al (18) showed that cyanide selectively potentiates the NMDA receptor influx of calcium possibly by interacting directly with the NR2A receptor subunit. The purpose of the present study is to investigate the mechanism by which cyanide enhances NMDA-mediated Ca ‫ם2‬ influx in neuronal cells.…”
Section: ‫ם2‬mentioning
confidence: 99%